Penerapan Pembelajaran Guru PAI Dengan Pendekatan Kontekstual Untuk Meningkatkan Prestasi Belajar Peserta Didik Di SMAIT Al Fahmi Boarding School Palu Mantikulore - Madinah (UNISAN JURNAL, 2025)
This study aims to examine the implementation of Islamic Religious Education (PAI) learning through a contextual approach. The method used is a qualitative research method. The contextual approach in PAI learning has great potential in improving student learning outcomes at SMAIT Al Fahmi Boarding School Palu Mantikulore. Through this approach, there are several important aspects that can be highlighted, namely: 1) Increasing active student participation; 2) Strengthening in-depth understanding of the material; 3) Sharpening critical thinking skills, because students are invited to analyze, evaluate, and make decisions based on Islamic teachings; 4) Encouraging the application of Islamic values ​​in everyday life. Thus, the contextual approach in PAI learning at SMAIT Al Fahmi Boarding School Palu Mantikulore can be an effective strategy to improve students’ academic achievement, broaden their understanding of Islamic teachings, and encourage them to practice these values ​​in real life.